COVID-19 pandemic’s broadcast media messages’ consumption in rural community and behavioral change - Blessed Frederick Ngonso; Obinna Johnkennedy Chukwu (International Journal of Communication and Society, 2021)
This study adopts FGDs as a research method. The discussion process was conducted in four different quarters that make up the community with 25 participants. Four research questions were formulated to guide the course of investigation. The findings of the study showed that a large portion of the community members are exposed to media messages on COVID-19 through the television. The findings also showed that, the community people particularly the educated ones watch TV on cable (GOTV and Startimes) and these are the people who shared information with family members, interpret it and take positive actions. While those who cannot read or write watch local NTA Auchi. These group of persons are few and mainly among the illiterate who source for news in local language.  A smaller proportion of the sample also affirmed that they do not watch TV or listen to radio for COVID-19 information due to hunger. This group maintained that they only watch Zee World channel. The findings also showed that no group talked about radio with emphasis. It is therefore, agreed that the rural community people in Iyamho do not depend on radio for information including COVID-19 information. In conclusion, the researchers agreed that rural dwellers of Iyamho are exposed to COVID-19 information on TV and the information has shaped their behavior by their interpretation of the messages received. The researchers also conclude that, radio is no longer fashionable in the rural community. It is therefore, recommended that subsequent studies on rural dwellers media message consumption should painstakingly interrogate the influence of social media. Again, in the future, if there is need for health awareness campaign, the government and health agencies should consider the use of traditional media to pass the information across to rural dwellers since illiterate folks still exit in the rural communities. TV information on health matters should be translated in rural languages on TV stations that are on GOTV and Startimes cables.